Tertiarisation without a competitive industrial base? An empirical analysis of shifts in the sectoral structure of employment in the münsterland and in the emscher-lippe region - Meyer, Bernd; Ewerhart, Georg; Siebe, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Within the discussion on strategies to bring down unemployment, great hopes have been placed in the services sector. Many people have already come to see services as the powerhouse of economic growth in the Federal Republic of Germany. However, this thesis fails to take account of the mutual dependencies which exist between the secondary and tertiary sectors. Empirical analysis for the Münster region administrative district illustrates the importance of the role played by upstream relationships between these two sectors. Consequently, the successes of the services sector in terms of job-creation are dependent on the competitiveness of the region’s industries. Providing support for the services sector without at the same time taking measures to nurture the industrial base would thus appear to be a highly questionable strategy.